An energy-saving method to solve the mismatch between installed and demanded power in hydraulic press. (15th December 2016) - Li, Lei; Huang, Haihong; Liu, Zhifeng; Li, Xinyu; Triebe, Matthew J.; Zhao, Fu
Abstract: Improving the energy efficiency of hydraulic presses has become an important field of research in low-carbon manufacturing systems. The mismatch between installed and demanded power is the main cause of low energy efficiency among hydraulic presses. This study presents an energy-saving method to solve the problem, where a single drive system composed of several motor-pumps, is partitioned into several drive zones corresponding to load profiles. The system is used to supply power to several hydraulic presses with approximately same installed power. Each drive zone is shared by grouped hydraulic presses in the same operation. Furthermore, a method for scheduling drive zones is presented to share drive zone with no conflict and shorten their idle time. The composition of each drive zone is optimized to match the power demand of each operation to achieve the scheduling schemes. The proposed energy-saving method is applied to a hydraulic press group in the case study. Results show that the energy efficiency of a single hydraulic press in the group is increased by approximately 20% and the average energy consumption can be reduced by 43% compared with the traditional setup.